Expressive Illocutionary Acts in Eye Candy Comic - Supri, Ida Zuraida (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to identify the types and analyze the functions of illocutionary acts in a comic entitled Eye Candy. The source of the data is a comic written by an Indonesian teenager. The descriptive method is employed in this research with the following stages: reading the comic, identifying utterances containing expressive illocutionary acts, categorizing the utterances into types of expressive illocutionary acts, and analyzing the function of the expressive illocutionary based on its context. This research uses the theory of types of speech acts and their functions proposed by Leech (1983. The results of the research show that (1) there are five kinds of expressive illocutionary acts found in Eye Candy Comic: thanking (33%), the second apologizing (23,5%), the third praising (20%), the fourth is complaining (13%), and finally, the fifth is blaming (10%). (2) The four illocutionary functions convivial or pleasant use, competitive, collaborative, and conflictive are found in the utterances.